Development of auditing in Malaysia: Legal, political and historical influences - Md Ali, Azham; Lee, Teck Heang; Mohamad Yusof, Nor Zalina; Ojo, Marianne (Social Science Electronic Publishing, 2007)
This work investigates the role and contribution of external auditing as practised in the Malaysian society during the forty year period from independence in 1957 to just before the onset of the Asian Financial Crisis in 1997.It applies the political economic theory introduced by Tinker (1980) and refined by Cooper & Sherer (1984), which focuses on the social relations aspects of professional activity rather than economic forces alone.In a case study format where qualitative data was gathered mainly from primary and secondary source materials, the study found that the function of auditing in the Malaysian society in most cases is devoid of any essence of mission; instead it is created, shaped and transformed by the pressures which give rise to its development over time.The largely insignificant role that it serves is intertwined within the contexts in which it operates.